Industrial organization : competition, strategy, policy - Lipczynski, John.; Wilson, John O. S.; Goddard, John A.; Lipczynski, John. (Harlow, England ; New York : Prentice Hall/Financial Times, 2005)
This new edition of 'Industrial Organization' improves on the success of the first edition to provide a strong link between the theory and analysis of industrial economics and to give real world application of the theory to the business environment.
Rev ed. of: Institutional organisation / John Lipczynski, John Wilson. 2001.
Includes bibliographical references (p. [735]-769) and index.
oif 11/11/14
Loan
Keywords: Industrial organization (Economic theory); Managerial economics